Farklı Saklama Koşullarının Taşköprü Sarımsağının (Allium sativum L.) Radyometrik ve Element İçeriği Üzerine Etkileri - Kurnaz, Aslı; Turfan, Nezahat (Turkish Science and Technology Publishing (TURSTEP), 2017)
Garlic is very rich plant in terms of carbohydrates, enzymes, sulphurous and phenolic compounds, proteins and vitamins. At the same time, natural and artificial radionuclides and heavy metals can be found in the garlic depending on the structure of the cultivated soil. Garlic, used as medicine in the treatment of most diseases, is also consumed as raw, powder, mash and volatile garlic oil. In this study, the effects of different storage conditions on the element and radionuclide content of the garlic were determined. The results obtained from this study were compared with the limit values of international institutions. As a result, the radionuclide concentrations and element contents of Taşköprü Garlic will not pose any threat to human health even if the garlic is exposed to different storage conditions.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health